Perinatal Asphyxia in Rat Alters Expression of Novel Schizophrenia Risk Genes - Paparelli, Alessandra; Iwata, Keiko; Wakuda, Tomoyasu; Iyegbe, Conrad; Murray, Robin M.; Takei, Nori (Frontiers in Molecular Neuroscience, 2017)
Epidemiological studies suggest that obstetric complications, particularly those related to hypoxia during labour and delivery, are a risk factor for development of schizophrenia. The impact of perinatal asphyxia on postnatal life has been studied in a rodent model of global hypoxia, which is accompanied by caesarean section birth. This asphyxia model shows several behavioural, pharmacological, neurochemical, and neuroanatomical abnormalities in adulthood that have relevance to schizophrenia. Further, it is suggested that schizophrenia has a strong genetic component, and indeed novel candidate genes were recently identified by a genome-wide association study. Here, we examined alteration in the novel schizophrenia risk genes, CNNM2, CSMD1, and MMP16 in the brains of rats undergoing caesarean section with or without global hypoxia. The brain regions studied were the prefrontal cortex, striatum, and hippocampus, which are all relevant to schizophrenia. Risk gene expression was measured at three time periods: neonatal, adolescence, and adulthood. We also performed an in vitro analysis to determine involvement of these genes in CNS maturation during differentiation of human neuronal and glial cell lines. Cnnm2 expression was altered in the brains of asphyxia model rats. However, Csmd1 and Mmp16 showed altered expression by exposure to caesarean section only. These findings suggest that altered expression of these risk genes via asphyxia and caesarean section may be associated, albeit through distinct pathways, with the pathobiology of schizophrenia.